UPDATE ON THE PHARMACOLOGICAL ACTIVITY OF VINCRISTINE FROM TAPAK DARA (CATHARANTHUS ROSEUS L.) - Muslikh, Faisal Akhmal; Prasetyawan, Fendy (PT. Intelek Cendikiawan Nusantara, 2024)
Indonesia ranks second in terms of terrestrial biodiversity after Brazil. Around 15,000 plant species in Indonesia have the potential for medicinal use, but only about 7,000 species have been utilized as raw materials for medicine. One common plant in Indonesia is the periwinkle (Catharanthus roseus L.), which grows both wild and cultivated as an ornamental plant. This plant has various benefits, including its potential as an anticancer agent due to the presence of vincristine and vinblastine compounds. This study aims to present the latest information on pharmacological activity testing of vincristine, in addition to its documented use as an anticancer agent. The methodology of this research was conducted using the Way2Drug webtool (https://www.way2drug.com/passonline/predict.php), with the SMILES of the vincristine compound obtained from PubChem (https://pubchem.ncbi.nlm.nih.gov/). The results showed that vincristine has a very high potential for cytostatic activity based on a Pa value (probability